Clinical course of 161 untreated and tenofovir‐treated chronic hepatitis B pregnant patients in a low hepatitis B virus endemic region. Issue 1 (20th July 2015) - Samadi Kochaksaraei, G.; Castillo, E.; Osman, M.; Simmonds, K.; Scott, A. N.; Oshiomogho, J. I.; Lee, S. S.; Myers, R. P.; Martin, S. R.; Coffin, C. S.
Summary: Hepatitis B immunoprophylaxis failure is linked to high maternal viraemia. There is limited North American data on hepatitis B outcomes in pregnancy. Pregnant hepatitis B carriers were enrolled January 2011–December 2014 and offered tenofovir in the 3rd trimester if hepatitis B virus (HBV)‐DNA was >7‐log IU/mL. Outcomes were determined in treated vs untreated patients. In total, 161 women with 169 pregnancies (one twin, 170 infants; median age 32 years), 18% (29/161) HBeAg+ and median HBV‐DNA 2.51 log IU/mL (IQR 1.66–3.65; range 0.8–8.1) were studied. 14.3% (23/161) received tenofovir due to high viral load (16/23, median 74 days, IQR 59–110) or due to liver disease (7/23). In 10/16 treated due to high viraemia, with confirmed adherence, follow‐up HBV‐DNA showed a 5.49 log decline ( P = 0.003). In treatment naïve mothers, median alanine aminotransferase (ALT) increased from 17 IU/L (IQR 12–24) to 29 (IQR 18–36) post‐partum ( P = 1.5e‐7). In seven highly viraemic mothers who declined therapy (HBV‐DNA >8‐log IU/mL); median ALT increased 3X from baseline ( P < 0.01). 26% (44/169) had Caesarean section with no difference in treated vs untreated subjects. No tenofovir‐treated mothers had renal dysfunction. Data were available on 167/170 infants; in 50.8% (85/167) who completed immunoprophylaxis, 98.8% (84/85, including 12 exposed to tenofovir in utero ) were HBV immune. One infant born to an HBeAg+ mother with HBV‐DNA >8‐log IU/mL failed immunoprophylaxis. In this prospective Canadian cohort study, most untreated mothers experienced mild HBV flares. Tenofovir in pregnancy is well tolerated and reduces viral load prior to parturition.